Cardiotoxicity in chemotherapeutic agents - Vitorino Modesto dos Santos; Lister Arruda Modesto dos Santos (Russian Open Medical Journal)
This Letter to the Editor aims to comment on the review by Duplyakov DV et al. published in this Journal, didactically discussing the cardiotoxicity in chemotherapy under the pathophysiological points of view as well as daily practical aspects. The growth of the oldest age groups of patients and the increased number of malignant entities undergoing chemotherapy enhances the significance of the cited work. One of the key points is the emphasis on the possibility of a known risk of cardiovascular damage due to chemotherapy surpass that of the malignancy under treatment. An additional short comment is about reversible cardiotoxicity in a 54-year-old Brazilian woman with breast cancer treated by trastuzumab. The herein commented articles can contribute to better understanding of mechanisms in cardiotoxicity related to chemotherapy, and to reduce the under diagnosis.